1972
DOI: 10.1002/cber.19721050508
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische Oxydation von Azido‐Zuckern. 3‐Amino‐3‐desoxy‐D‐glucuronsäure und 4‐Amino‐4‐desoxy‐D‐glucuronsäure

Abstract: Am C-1 geschiitzte Azido-aldosen konnen bei Gegenwart eines Platinkatalysators mit Sauerstoff zu entsprechenden Azido-uronsluren oxydiert werden, die leicht durch Hydrierung in Amino-uronsluren uberfuhrbar sind. Damit ist ein vereinfachter Syntheseweg zu Aminouronsluren gegeben. Das Verfahren wurde zur Darstellung von 3-Azido-3-desoxy-l.2-0isopropyliden-a-D-glucofuranuronsaure (6) und Methyl-4-azido-4-desoxy-a-~-glucopyranosiduronsaure (15) erprobt. 3-Amino-3-desoxy-~-g~ucopyranuronsaure (11) und einige ihrer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We mentioned above that the next hurdle in our route might be the selective oxidation of the primary hydroxy group. We tried several methods—including variants which first provide an intermediate aldehyde20, 7 to be further oxidized into the carboxylic acid—but finally found that direct oxidation of 29 with platinum dioxide and oxygen provided the most satisfactory result 21, 15c. The generated carboxylic acid immediately cyclized to δ ‐lactone 30 , isolated in 66 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…We mentioned above that the next hurdle in our route might be the selective oxidation of the primary hydroxy group. We tried several methods—including variants which first provide an intermediate aldehyde20, 7 to be further oxidized into the carboxylic acid—but finally found that direct oxidation of 29 with platinum dioxide and oxygen provided the most satisfactory result 21, 15c. The generated carboxylic acid immediately cyclized to δ ‐lactone 30 , isolated in 66 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Removal of the isopropylidene resulted in formation of amino allouronic acid ( Figure 7). [23] Ogawa later published the synthesis of a 3-amino-3,4-dideoxyhexuronic acid in route to ezomycin. [23] Ogawa later published the synthesis of a 3-amino-3,4-dideoxyhexuronic acid in route to ezomycin.…”
Section: Syntheses Of Natural Amino Hexuronic Acidsmentioning
confidence: 99%
“…Reduction of the epoxide syn- (10) provided the desired syn-amino alcohol (11) in 74% yield (m.p. 84.5-85.5 "C,…”
Section: An Efficient Stereocontrolled Synthesis Of (-)-Detoxininementioning
confidence: 99%